Simulation study of cutting fluid flow field in kerf of fine diameter diamond wire saw - Jiahu CHEN; Peiqi GE (Jin'gangshi yu moliao moju gongcheng)
Objectives: Electroplated diamond wire saws are widely used in the field of slicing hard and brittle materials such as monocrystalline silicon and sapphire. Cutting fluid should give full play to its role in the sawing process, which is conducive to the improvement of wafer quality. As the size of the wafer increases and the diameter of the wire saw decreases, the kerf in the sawing process becomes deeper and narrower, and the cutting fluid cannot enter the kerf in large quantities, resulting in worse lubrication and cooling effects during the sawing process, which leads to the decline of the surface quality of the wafer. Based on computational fluid dynamics (CFD) numerical simulation methods, the cutting fluid flow field in the cutting seam of the diamond wire saw was analyzed and studied. Methods: In this paper, based on CFD numerical simulation methods, the cutting fluid flow field in the sawing seam of the diamond wire saw is analyzed and studied. Firstly, according to the actual situation of the diamond wire saw cutting process, a 3D simulation geometric model is established based on the liquid supply mode, where cutting fluid flows along the sawing wire and is brought into the sawing area by the motion of the sawing wire. Heat transfer is not considered in this study, and the cutting fluid is assumed to be a viscous incompressible fluid. The governing equations of fluid flow include the continuity equation and the momentum equation. It is found from the equations that the main factors affecting the flow field distribution of cutting fluid in the kerf are wire speed and cutting fluid density. By calculating Reynolds number and Weber number, the fluid model studied in this paper is selected as the Transition SST model. The VOF method is determined to characterize the fluid state of cutting fluid in the saw joint, and the CSF model is introduced into the VOF method to characterize the influence of surface tension. Considering the influence of physical properties of cutting fluid, the density, viscosity, surface tension, and wall contact angle of cutting fluid are measured experimentally. The momentum equation is solved by a pressure-based solver, the continuity equation is solved by implicit time discretization, and the PISO method is used for pressure-velocity coupling. Result: With the increase of chip size and the decrease of wire saw diameter, the size of the saw seam is getting smaller and smaller. The main fluid entering the saw seam is shear flow, and the main factor affecting the fluid motion state is the wire speed. Under the condition of small-size sawing, when the wire speed is low (vw≤25 m/s), both the contact area and the non-contact area of the saw wire in the sawing joint are not completely filled with liquid, and the liquid volume fraction in the contact area is < 100%, with an air layer in the area. With the increase of wire speed, more and more cutting fluid enters the sawing joint. With the increase of wire speed, more and more cutting fluid enters the saw seam. When vw>25 m/s, both the contact area and the non-contact area are filled with liquid. The cutting fluid pressure in the saw seam increases with the increase of wire speed on both the contact area side and the non-contact area side, and the pressure difference on both sides also increases generally. The pressure distribution on both sides becomes more stable. After both sides of the saw seam are filled with liquid, the pressure on one side of the contact area is about 0.1790 MPa, and the pressure on one side of the non-contact area is about 0.1590 MPa. With the gradual reduction of the viscosity and surface tension of the cutting fluid, the cutting fluid gradually fills the saw joint. Howver, when the viscosity and surface tension of the cutting fluid are too small, the cutting fluid entering the saw joint will tend to decrease. The cutting fluid pressure in the saw seam increases with the decrease of the cutting fluid viscosity and surface tension in both the contact area and the non-contact area, and the pressure distribution becomes more stable. However, when the viscosity and the surface tension are too small, the pressure will also fluctuate. Under the physical properties of the cutting fluid C, with a density of 872.5 kg·m−3, viscosity of 1.15 mPa·s and surface tension of 34.02 mN·m−1, the pressure distribution of the cutting fluid on the contact area side and the non-contact area side is more stable. The maximum pressure on the contact area side is about 0.0169 MPa, and the maximum pressure on the non-contact area side is about 0.0132 MPa. Conclusions: (1) Under small sawing sizes, when the wire speed is low, the cutting fluid is difficult to fully enter the sawing area to play its role. With the increase of the wire speed (vw>25 m/s), the contact area and non-contact area between the saw wire and the workpiece are gradually filled with liquid, and the cutting fluid pressure and pressure difference between the contact area and the non-contact area show an overall increasing trend. When the contact area and non-contact area are full of cutting fluid, the cutting fluid pressure distribution in the saw joint is relatively stable, with the pressure in the contact area being about 0.1790 MPa and the pressure in the non-contact area being about 0.1590 MPa. (2) The reduction of liquid viscosity and surface tension within a certain range is conducive to ensuring the relative saturation and stability of the cutting fluid in the saw joint, and at the same time, it can make the pressure distribution of the cutting fluid in the saw joint more stable. A comprehensive comparison of the physical properties of the 5 groups of cutting fluids shows that the physical properties of the cutting fluid C during the diamond line saw cutting process are more conducive to its entry into the saw joint.